2019
DOI: 10.1088/1757-899x/710/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the 3D printout filling parameter on the impact strength of elements made with the FDM method

Abstract: The paper discusses the aspects of potential use of 3D printing technology in the process of manufacturing elements with different layer fillings. In 3D printing technology, the denser the percentage of filling a material, the higher the mechanical strength of a given element. However, in the literature on the subject, the dependence on these parameters for additive technology has not been unequivocally determined. Therefore, the aim of the study is to find a correlation between the internal structure of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Numerous studies have examined how filling patterns and infill density affect specimen mechanical characteristics. Impact strength, elongation, and tensile strength have been discovered to be influenced by the infill density and raster direction [ 24 , 25 , 26 ]. It has been discovered that the internal architecture or infill pattern affects flexural features, friction coefficient, Poisson’s ratio, and stress values [ 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have examined how filling patterns and infill density affect specimen mechanical characteristics. Impact strength, elongation, and tensile strength have been discovered to be influenced by the infill density and raster direction [ 24 , 25 , 26 ]. It has been discovered that the internal architecture or infill pattern affects flexural features, friction coefficient, Poisson’s ratio, and stress values [ 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, a large number of scholars have studied the mechanical properties of ME products, such as tensile strength, [6][7][8][9] fracture toughness, [10][11][12] impact strength, [13][14][15][16] and fatigue property. [17][18][19] Many studies have shown that processing parameters have a significant effect on the performance of ME products.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element method is used to solve various problems in engineering by using FEM software packages. Numerical simulation of solidification facilitates obtaining highquality castings and minimising product cost and scrap [1][2][3][4]. FEM-based software for solving casting problems has high computational capabilities for low operating costs, and advances in simulation methodology have made simulation the most widely used and accepted method in operations research and systems analysis.…”
Section: Introductionmentioning
confidence: 99%